Design Of Power Amplifier For Ultra-Wideband (UWB) Applications Using Silterra 0.18 μm Cmos Technology - Yap, Hock Lian (Universiti Sains Malaysia, 2006)
A power amplifier for Ultra-Wideband (UWB) transceiver system is presented. UWB is a high data rates (up to 480 Mbps) wireless communication technology for short distance (less than 10m) applications. UWB technology is a low power (-41.3 dBm/MHz) wireless communications that can coexist with the existing technology such as Bluetooth, GPS (Global Positioning System) and WiFi. The power amplifier is designed for UWB direct conversion (DICON) transceiver system that employs Multi-band Orthogonal Frequency Division Multiplexing (MB-OFDM) approach and operates in mode 1 (3.1 to 4.9GHz) of UWB spectrum. The power amplifier is designed using Silterra 0.18μm CMOS technology in three different version which consists of IDEAL, SIL18RF and ASITIC case. The power amplifier has been implemented in two versions which are SIL18RF inductor and ASITIC inductor. IDEAL case achieved S11 < -31 dB, S12 < -75 dB, S21 = 19.45 ± 0.64 dB and S22 < -10 dB. IDEAL version also achieved input referred 1 dB compression point of -17.44 dBm and maximum output power of 1.49 dBm while consuming only 31.3 mW. On the other hand, SIL18RF version achieved S11 < -10 dB, S12 < -82 dB, S21 = 16.39 ± 0.68 dB and S22 < -10.3 dB while ASITIC version achieved S11 < -25 dB, S12 < -82 dB, S21 = 19.66 ± 1.45 dB and S22 < -10.8 dB. SIL18RF version obtained input referred 1 dB compression point of -14.4 dBm and maximum output power of 1.38 dBm while ASITIC version achieved input referred 1 dB compression point of -13.57 dBm and maximum output power of 2.12 dBm. SIL18RF and ASITIC version only consume 30.87 mW and 31.63mW respectively. The layout dimension of SIL18RF version is 3.7mm x 2.6mm which is bigger than ASITIC version estimated to be 0.55mm x 0.85mm. A PCB (Printed Circuit Board) with dimension of 60mm x 80mm has been designed to characterize SIL18RF fabricated chip. Beside power amplifier design, a measurement task has been carried out to evaluate the performance of MAX2242EVKIT using radio frequency high end tools. From measurement results, MAX2242 can produce +26 dBm output power at 5 dBm input power and 3.3V power supply.